Kontribusi Pembela Tanah Air (PETA) dalam Pembentukan TNI dengan Pendekatan Historis dan Ilmu Pertahanan - Abdi Manab Idris; Suyono Thamrin; Donny Yoegiantoro; Rinaldo Albertus Triprasetyo (Mahesa Research Center, 2022)
The purpose of this study is to analyze and examine the social phenomenon of the formation of the TNI. This research is focuses on elevating the role and contribution of PETA in the formation of the TNI in terms of history and defense science. The research method used is a literature study method with a qualitative approach. The results showed that the Republic of Indonesia in general had been colonized by several European countries such as the Netherlands, Portugal and Japan. However, the suffering of colonialism was most felt when the Japanese Occupation Period formed the Defender of the Homeland Army (PETA). PETA is a security institution that was formed during the Japanese occupation of Indonesia in September 1943. PETA has contributed a lot to the forerunner of the Unitary State of the Republic of Indonesia since before independence in the form of defiance and resistance to the Japanese army, securing the independence procession and being the first to raise the saka red and white. , changed its name to the People's Security Agency (BKR) to the Indonesian National Army (TNI). During the process of changing the name of the institution there have been several incidents ranging from rebellion to military aggression by the Dutch. As for the resistance and operations carried out ranging from guerrilla warfare, physical to non-physical. The Historical Approach is a condition of PETA's military since it was first formed until it turned into the TNI in various regions in Indonesia and the Defense Science Approach in the form of a tactical step/independence movement which led to PETA's contribution to Indonesia.